Subjective position sliding in utterances perceived as echolalic in a child with Language Disorder: a case study - Bonatto, Juliana [UNESP]; Coelho, Natália Faloni [UNESP]; Chacon, Lourenço [UNESP] (FapUNIFESP (SciELO), 2024)
Within a linguistic-discursive framework, subject markers in a chain of utterances considered to be echolalia based on the recurring linguistic structure does X want Y? were investigated. This chain was produced during a speech therapy session by J., a female child, 10-years-old at the time of data collection, and with a speech-language pathology diagnosis of language disorder and a medical diagnosis of early psychosis. A set of linguistic fluctuations indicated a sliding of the subject position in the analyzed chain. Such fluctuations involved syntactic, lexical, semantic, morphological and prosodic elements. Discursively, the fluctuations left traces of a sliding of the subject position in the chain formed by these utterances, from a spoken subject (do you want Y?) to a speaking/desiring one (I want Y.). In this way, utterances considered echolalia can provide clues, via their linguistic fluctuations and discursive slippages, about the subject’s desire in their relationship with the O/other. Given this, although they do not emerge in a conventional way, such utterances can demonstrate possibilities for changes in subject position. A contribution of the present research for clinical practice involving language in therapeutic settings therefore, was to highlight a listening to utterances, which could be seen as connected/grounded in the speech of the other. In clinical practice involving language, it is possible to create space for new/other senses for utterances, to allow the constitution of the subject of/in language, based on utterances often interpreted as being devoid of subjectivity.
Deslizamentos de posição subjetiva em enunciados tidos como ecolálicos de uma criança com Distúrbio de Linguagem: um estudo de caso
Keywords: Child Language; Distúrbio de Linguagem; Echolalia; Ecolalia; Fonoaudiologia; Language Disorder; Linguagem Infantil; Linguistics; Linguística; Speech Therapy